Usability Testing of a Collaborative and Interactive University on a Mobile Device - McArdle, Gavin; Monahan, Teresa; Bertolotto, Michela (International Journal of Interactive Mobile Technologies (iJIM), 2009)
Abstract - The use of mobile devices for delivering learning tools is an attractive concept. Termed mobile learning (m-learning), this new technology allows people to participate in learning activities without being tied to a fixed location and provides users with convenient and flexible access to learning resources anytime and anywhere. While many m-learning applications have been developed to date, most provide tools to help studentsâ?? with specific learning tasks rather than a general interface to online courses. Few sup-port online learning communities or allow users to download multimedia learning content. These features would engage mobile users and enable them to interact with one another, thus allowing them to participate in group learning activities despite their changing location. In this article, we describe an m-learning system which we have developed which aims to incorporate these facilities. This system provides access to multimedia learning resources and supports mobile users in an interactive synchronous learning environment with their desktop peers. Details of the evaluation techniques which we utilised to appraise the system are provided and the results are presented. Feedback suggests that the features offered by our system are beneficial for collaborative m-learning.